THEORETICAL FOUNDATIONS FOR THE STUDY OF LANGUAGE NOMINATION (World Bulletin of Social Sciences, 2023)
This article is written about theoretical foundations for the study of language nomination, the problem of studying language nomination in linguistics and language nominations of football teams, players and their non-verbal actions